Government Strategies for Palm Oil Trade Disputes After The 2021 Crude Palm Oil Phase-Out Policy - Suhendra, Dinda Maylinda (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The termination of the policy of using crude palm oil issued by the European Union Parliament which states that it is necessary to suppress the use of palm oil to a maximum of 7 as energy for its use aimed at transportation use by 2030 which will have an impact on CPO export producers, namely Indonesia and Malaysia, which will lose their market. With the impact of this problem, it will also affect the workers who have been making a living by working as oil palm day laborers. The research method used in this research is normative juridical. The results of this study are the Government's Strategy Regarding Coconut Oil Trade Disputes After the CPO Termination Policy is First, the ban on nickel ore exports since January 1, 2020 to the European Union, trade disputes that occur between Indonesia and the European Union can be resolved through the DSB at the WTO and the steps that can be taken are to approach the disputing parties based on the needs of each party